Developing an inclusive landscape management plan for doma-rutu social ecological landscape, Nigeria - Igbadun, H. E.; Ojeleye, O. A.; Oke, Adebayo; Atampugre, Gerald; Tilahun, Seifu A.; Ismail, H.; Jonathan, J.; Cofie, Olufunke O. (International Water Management Institute, 2024)
Landscape management planning is a collaborative process to ensure sustainable land and water use while addressing climate change. The Doma-Rutu Landscape in Nigeria faces challenges like deforestation, soil erosion, and limited institutional support. A multi-stakeholder approach was used to identify challenges, set goals, and develop strategies for the landscape. The goal is to create an Inclusive Landscape Management Plan (ILMP) to address these challenges and promote sustainable development.